A relação entre composição e performance no processo de criação: um estudo sobre a colaboração entre compositores e intérpretes - Joana Monteiro Radicchi (2013)
This dissertation presents a study about the collaboration between composers and performers during the creative process of musical works. The main axis of this study is the account of this interactive process as experienced by the composer, Leonardo Margutti, and myself during the composition of 'Inflexões' for C flute and alto flute. In search of parameters to aid in counterbalancing the collaborative experiment reported here, a historical contextualization was researched based on consecrated works for flute forged by way of this same contact between composer and performer. In addition, interviews with composers and performers active in this field of partnership were realized in order to obtain data about this type of interaction and its unfolding during the composition as well as the performance of a musical work.